Ngữ điệu tiếng Anh ở người Việt - Nguyễn, Huy Kỷ (H. : ĐHQGHN, 2017)
Our article consists of 6 parts: Introduction to English intonation for the English speaking Vietnamese, some basic notions concerned, some major criteria for the selection of the English intonation patterns/ models by the Vietnamese, the concept and theoretical -practical approaches, the models of English intonation by the Vietnamese, and the conclusion. Without the working criteria and investigation results mentioned in the article, it is totally hard for us to identify 5 English intonation models used by the Vietnamese in the authentic situations. Something more important is that the author has designed 25 situations for 25 uses of English intonation by the Vietnamese to function more effectively. For more details, the academic article is of great help to those who are interested in it